2022
DOI: 10.3390/foods11152273
|View full text |Cite
|
Sign up to set email alerts
|

AI-2/Lux-S Quorum Sensing of Lactobacillus plantarum SS-128 Prolongs the Shelf Life of Shrimp (Litopenaeus vannamei): From Myofibril Simulation to Practical Application

Abstract: Retarding the protein deterioration of shrimp during storage is important for maintaining its quality. Lactobacillus plantarum SS-128 (L. plantarum SS-128) is a biocontrol bacterium that can effectively maintain the fresh quality of food. This research establishes a myofibril simulation system and refrigerated control system to explore the impact of L. plantarum SS-128 on the quality and shelf life of refrigerated shrimp (Litopenaeus vannamei). Through the bacterial growth assay and AI-2 signal molecule measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The anti-QS activity of Bacillus strains was identified through the QQ activity of lactonase and the antagonistic effect of DKPs on QS receptors. Li et al (2022a) [ 81 ] showed that QS promoted the growth of Lb. plantarum ss-128, but they did not investigate its anti-QS activity against spoilage bacteria.…”
Section: Mechanism Of Qs Inhibitionmentioning
confidence: 99%
“…The anti-QS activity of Bacillus strains was identified through the QQ activity of lactonase and the antagonistic effect of DKPs on QS receptors. Li et al (2022a) [ 81 ] showed that QS promoted the growth of Lb. plantarum ss-128, but they did not investigate its anti-QS activity against spoilage bacteria.…”
Section: Mechanism Of Qs Inhibitionmentioning
confidence: 99%